'Jumping the first hurdle': Framing action research questions using the Ice Cream Cone Model. Issue 3 (November 2017) - Brownhill, Simon; Ungarova, Talash; Bipazhanova, Aiman
The importance of good research questions is well recognised in the research community. The difficulty lies in actually formulating these research questions, an issue which both beginning and established researchers have expressed concerns about. This article reports on an innovative framing device which was developed for international trainers and teachers to help them 'jump the first hurdle' and write a 'good' research question to specifically drive a cycle of action research. Through a staged exploration of the thoughts and perceptions of Kazakhstani trainers who used the Ice Cream Cone Model, findings highlight strong support for the use of the framing device and the 'logical steps' it provides for producing small-scale action-based research questions. The value of this framing device for teacher researchers and those involved in supporting teachers to carry out action research will be considered following an exploration of model-generated research questions.